2023
DOI: 10.1186/s43058-023-00448-w
|View full text |Cite
|
Sign up to set email alerts
|

mHealth to improve implementation of TB contact investigation: a case study from Uganda

Abstract: Background Implementation science offers a systematic approach to adapting innovations and delivery strategies to new contexts but has yet to be widely applied in low- and middle-income countries. The Fogarty Center for Global Health Studies is sponsoring a special series, “Global Implementation Science Case Studies,” to address this gap. Methods We developed a case study for this series describing our approach and lessons learned while conducting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
2
0
1
Order By: Relevance
“…These studies have demonstrated the strengths of utilizing the CFIR in various types of research, including qualitative [ 54 , 55 , 65 67 , 69 , 71 , 73 , 75 , 77 , 79 ], quantitative [ 53 ], mixed methods [ 76 ] and case studies [ 72 ]. Qualitative studies have employed the CFIR as an interview design and guide and collection tool to explore the perspectives and engagement of healthcare system stakeholders concerning implementation readiness [ 54 , 55 , 65 67 , 69 , 71 , 73 , 75 , 77 , 79 ]. However, it should be noted that the success of information capture may vary across specific constructs [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have demonstrated the strengths of utilizing the CFIR in various types of research, including qualitative [ 54 , 55 , 65 67 , 69 , 71 , 73 , 75 , 77 , 79 ], quantitative [ 53 ], mixed methods [ 76 ] and case studies [ 72 ]. Qualitative studies have employed the CFIR as an interview design and guide and collection tool to explore the perspectives and engagement of healthcare system stakeholders concerning implementation readiness [ 54 , 55 , 65 67 , 69 , 71 , 73 , 75 , 77 , 79 ]. However, it should be noted that the success of information capture may vary across specific constructs [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…It helped identify factors that promote or undermine implementation success, guiding practical and programmatic implications. Additionally, it also allowed for the evaluation of scalability and generalization across cities and countries [ 55 , 66 , 68 , 69 , 73 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oleh karena ulasan di atas dapat menjadi salah satu penguat bahwa pemantauan melalui penerapan teknologi digital diharapkan mampu menjadi salah satu solusi untuk meningkatkan pengobatan pasien Tuberkulosis Paru pada fase lanjutan/jangka panjang hingga dinyatakan tuntas (Balaji et al, 2022;Gashu et al, 2021;Gupta et al, 2023;Turimumahoro et al, 2022). Dengan adanya pengingat melalui SMS atau pengingat lainnya pasien akan merasa terbantu dan merasa diperhatikan dalam menginat jadwal meminum obat.…”
unclassified